Epidemiology, Clinical Features and Prognostic Factors of Pediatric SARS-CoV-2 Infection: Results From an Italian Multicenter Study - Garazzino, Silvia; Lo Vecchio, Andrea; Pierantoni, Luca; Calò Carducci, Francesca Ippolita; Marchetti, Federico; Meini, Antonella; Castagnola, Elio; Vergine, Gianluca; Donà, Daniele; Bosis, Samantha; Dodi, Icilio; Venturini, Elisabetta; et al. (Frontiers in Pediatrics, 2021)
Background: Many aspects of SARS-CoV-2 infection in children and adolescents remain unclear and optimal treatment is debated. The objective of our study was to investigate epidemiological, clinical and therapeutic characteristics of pediatric SARS-CoV-2 infection, focusing on risk factors for complicated and critical disease. Methods: The present multicenter Italian study was promoted by the Italian Society of Pediatric Infectious Diseases, involving both pediatric hospitals and general pediatricians/family doctors. All subjects under 18 years of age with documented SARS-CoV-2 infection and referred to the coordinating center were enrolled from March 2020. Results: As of 15 September 2020, 759 children were enrolled (median age 7.2 years, IQR 1.4; 12.4). Among the 688 symptomatic children, fever was the most common symptom (81.9%). Barely 47% of children were hospitalized for COVID-19. Age was inversely related to hospital admission (p < 0.01) and linearly to length of stay (p = 0.014). One hundred forty-nine children (19.6%) developed complications. Comorbidities were risk factors for complications (p < 0.001). Viral coinfections, underlying clinical conditions, age 5–9 years and lymphopenia were statistically related to ICU admission (p < 0.05). Conclusions: Complications of COVID-19 in children are related to comorbidities and increase with age. Viral co-infections are additional risk factors for disease progression and multisystem inflammatory syndrome temporarily related to COVID-19 (MIS-C) for ICU admission.